Dehydrogenative Sn–E (E = S, Se) bond formation catalyzed by an iron complex. Issue 5 (4th December 2018) - Itazaki, Masumi; Ogawa, Yudai; Nakamura, Wataru; Nakazawa, Hiroshi
Abstract: Iron complex‐catalyzed dehydrogenative Sn–E (E = S, Se) bond formation of hydrostannane with thiol and selenol was achieved. All new compounds were fully characterized using 1 H, 13 C 1 H, 77 Se 1 H, and 119 Sn 1 H NMR measurements and elemental analyses. The structure of 1, 1′‐(1, 3‐dithia‐2, 2‐dibutylstanyl)‐[3]ferrocenophane was confirmed by single‐crystal X‐ray diffraction.